University Guidance Actions in the Pos-COVID Era: Returning to the Classroom - Vidal-Martí, Cristina (2022)
Introduction: The return to the classroom after a long period of online, training due to the COVID-19 pandemic, entailed a process of adaptation for both students and teachers. This article explains a teaching proposal in a third year Pedagogy course to facilitate the process of returning to the classroom. Objectives: Accompany students, especially those who have difficulties, create a good climate of support and mutual help, as well as reinforce participation and involvement. Method: Use of the flipped classroom methodology, cooperative work in a small group, reinforcement of feedback in the return of evaluable activities and activities that promote self-efficacy. Discussion: The experience is in process of evaluation. However, the available data through the evaluation instruments allow us to affirm that the psychopedagogical orientation is a facilitating strategy for the adaptation process of the students.